USING COMMUNICATIVE APPROACH TO ENHANCE SPEAKING SKILLS: USING COMMUNICATIVE APPROACH TO ENHANCE SPEAKING SKILLS - Jambulova, Ayimkhan (Журнал иностранных языков и лингвистики, 2025)
Speaking is very important in human life. Speaking is one of the components in teaching English. Speaking is a process in which speaker expresses his/her thoughts, ideas, experiences, opinions, perception through spoken language. Using language by speaking, human are allowed to communication with other people to express ideas, to facilitate the thinking process and to recall the information. Speaking is one of the skills that the students will be judged upon most in a real-life situation. Speaking is a productive skill that often presents challenges due to its spontaneous and interactive nature.